Burkitt’s Lymphoma in a Post-renal Transplant Recipient: A Rare and Aggressive Malignancy - Divya Dagaji Jadhav; Abhijeet Sugriv Ghodke; Sushil Kachewar; Kranthi Dandi (Journal of Clinical and Diagnostic Research)
Burkitt lymphoma is a highly aggressive form of non-Hodgkin B-cell lymphoma known for its rapid proliferation. It commonly involves areas such as the jaw, abdominal region, or Central Nervous System (CNS). This type of lymphoma is often associated with infections like Epstein-Barr Virus (EBV) and Human Immunodeficiency Virus (HIV). Additionally, it frequently features chromosomal translocations that affect the MYC oncogene. The case involves a 34-year-old man with diabetes who has been undergoing immunosuppressive treatment for 10 years following a kidney transplant. He presented with complaints of lower abdominal swelling, nausea, vomiting, and backache for the past 15 days, along with signs suggestive of intestinal obstruction for the last five days. Comprehensive history-taking, clinical examination, and diagnostic investigations indicated an intestinal obstruction caused by a mobile intra-abdominal mass located in the suprapubic region. An ultrasound-guided Tru-Cut biopsy of the intra-abdominal mass identified it as Non-Hodgkin Lymphoma (NHL), most likely Burkitt Lymphoma (BL), which was subsequently confirmed through Immunohistochemistry (IHC). The patient was managed with Rituximab (a monoclonal antibody), and his immunosuppressive therapy was continued. However, he showed a poor response to treatment after four weeks, prompting a revision of the regimen to the Cyclophosphamide, Vincristine, Doxorubicin, and High-Dose Methotrexate/Etoposide, Ifosfamide, and Cytarabine (CODOX-M/ IVAC) chemotherapy protocol. The aim of this paper presentation is to highlight the rarity of the disease and the management of a patient on immunosuppressant therapy following an organ transplant.